Atypical antipsychotics in the treatment of children and adolescents with pervasive developmental disorders - Politte, Laura C.; McDougle, Christopher J. (Psychopharmacology, 2014)
Rationale Autism and related pervasive developmental disorders (PDD) are characterized by impairments in social interaction and communication, restricted interests, and repetitive and stereotyped patterns of behavior. Individuals with PDD frequently display irritability and disruptive behaviors including tantrums, self-injurious behavior, and aggression. Atypical antipsychotics are currently the most efficacious pharmacological interventions available for treatment of irritability associated with PDD. Objectives This article aims to review the body of literature pertaining to the use of atypical antipsychotics in the treatment of patients with PDD. Methods A PubMed literature search was conducted using the following key words: autism , pervasive developmental disorders , atypical antipsychotics , risperidone , aripiprazole , quetiapine , ziprasidone , olanzapine , clozapine , paliperidone , iloperidone , asenapine , and lurasidone . Search terms were limited to English language, human subjects, and publication from 1999 to present. Relevant references from identified articles were also reviewed. Results The efficacy and tolerability of risperidone and aripiprazole for the treatment of irritability in autism have been established with multi-site, randomized, controlled trials. Studies supporting the use of other atypical antipsychotics are either limited in scope or less robust in their findings, though newer agents such as ziprasidone and paliperidone show promise. Conclusions Atypical antipsychotics are currently first-line pharmacological agents for the treatment of irritability and associated behaviors in children with PDD. Further placebo-controlled studies are warranted to characterize the efficacy and tolerability of the majority of these medications. There is also a need for the development of novel, targeted drugs with more favorable long-term side effect profiles.